SUPPORT OF THE SOVIET STATE IN THE WORK OF TRAINING PERSONNEL OF ASIAN AND AFRICAN COUNTRIES - Sardor Shirinov Avazovich (Scholar Express Journal, 2022)
Today, the countries of the Asian and African continents are experiencing a different stage of development. In Asia, Japan is the only developed country that belongs to the group of” Big Seven», in addition, countries such as the Republic of Korea, Singapore, Israel are also among the developed countries. China and India are among the main developed countries with great potential in terms of natural resource, GDP, while Vietnam, Cambodia, Bangladesh, Sri Lanka, Iraq, the DPRK are the slow developing countries that are experiencing a transitional period. Most countries in Asia and Africa have long been colonized. National liberation movements, which took place in Asia in the formation or independence of such states as China(1949), Vietnam(1946), Laos, Iraq(1958), India (1947), North Korea(1948), Burma(1948) Mongolia (1921), were largely politically-economically supported by the Soviet state. Also, when these states were developing and restoring the destroyed economy, socialism began to create an economic model in shape
Keywords: Natural Resource; GDP; Developing Countries